BOARD DYNAMICS AND EARNINGS MANAGEMENT OF LISTED INDUSTRIAL GOODS FIRMS IN NIGERIA - Abubakar, Abubakar; Hassan, Shehu Usman (Kashere Journal of Management Sciences, 2024)
This study examines the impact of board dynamics on earnings management of listed industrial goods firms in Nigeria. The study adopted causal research design, the population of the study is made up the entire thirteen (13) industrial goods firms in Nigeria listed the floor of Nigerian Exchange group as at 31st December, 2022, census sampling technique was used to arrive at a sample size of thirteen (13) industrial goods firms. However, the data were extracted from annual reports and accounts of the sampled firms for the period of ten (10) from 2013-2022. The multiple regression was used as a techniques of data analysis, regression result shows that board gender, board nationality, board risk and board expertise has a negative and significant impact on earnings management of the sampled firms, while board reputation has a positive and insignificant impact on earnings management. Based on the findings, the study concluded that board gender, board nationality, board risk and board expertise reduce the earnings management. Board reputation does not affect earnings management. Based on findings and conclusion, it is therefore, recommends that the management of listed industrial goods companies in Nigeria should increase the presence of women directors on boards. The portion of female members on board should be 30% as proposed by the critical mass theory and that of male members should be 70% as this will help in reduce manipulating of earnings by the management.